2015
DOI: 10.1016/j.amepre.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Team-based Care in Controlling Blood Pressure

Abstract: Context High blood pressure is an important risk factor for cardiovascular disease (CVD) and stroke, the leading cause of death in the U.S. and a substantial national burden through lost productivity and medical care. A recent Community Guide systematic review found strong evidence of effectiveness of team-based care in improving blood pressure control. The objective of the present review was to determine from the economic literature whether team-based care for blood pressure control is cost-beneficial and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 53 publications
1
33
0
5
Order By: Relevance
“…13 Studies of SMBP within TBC included in the present review do not provide evidence for the contribution of SMBP to the effectiveness or cost effectiveness of TBC because the studies compared SMBP within TBC to usual care. However, SMBP is a common component of TBC for BP control, as it provides a regular and ongoing activity to engage patients in their own care.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13 Studies of SMBP within TBC included in the present review do not provide evidence for the contribution of SMBP to the effectiveness or cost effectiveness of TBC because the studies compared SMBP within TBC to usual care. However, SMBP is a common component of TBC for BP control, as it provides a regular and ongoing activity to engage patients in their own care.…”
Section: Discussionmentioning
confidence: 97%
“…An intervention is considered cost effective if the cost per QALY saved is less than a conservative threshold of $50,000. 11,12 The present review translated reductions in SBP to QALYs saved 13 to assess cost effectiveness for studies that reported the change in BP resulting from intervention. Two translations from the published literature were used: Translation (1), for which a reduction of 1 mmHg of SBP=0.009 QALY saved 14 ; and Translation (2), for which a reduction of 1 mmHg of SBP=0.093 QALY saved.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…For this reason, many instruments did not fully measure core attributes of the concept of team‐based care as identified in this analysis. Instead, those instruments focused more on antecedents, the effects of the antecedents, and consequences of team‐based care in this analysis (Goldberg et al., ; Helfrich et al., ; Jacob et al., ; Jesmin et al., ; Mitchell et al., ). For example, Helfrich et al.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, shortages in primary health care professionals will likely require expanding use of system approaches, collaborative relationships among health care professionals, and clinical‐community linkages to serve the greater number of adults needing new or intensified BP management and other related services. For example, team‐based models of care utilizing a diverse health care team—including nurses, nutritionists, and pharmacists—have been shown to be a cost‐effective strategy in BP management . Effective team‐based care often requires the integration of standardized hypertension treatment approaches (eg, protocols) to support communication between team members and help guide decision making, including the intensification of pharmacologic treatment .…”
Section: Discussionmentioning
confidence: 99%